Analysis Translation Methods of Text Translation in the Novel Al-Liṣ wa al-Kilāb by Najib Mahfuz - Choirun Nisa', Ummi; Shalihah, Imroatus; Qomari, Nur (Diwan: Jurnal Bahasa dan Sastra Arab, 2023)
Based on Peter Newmark's translation methodology theory, this study aims to identify and classify the accuracy of the use of diction in the novel Al-Lis} wa al-Kila>b. A descriptive qualitative approach was used in this research type. Reading techniques, document analysis, and sampling were used to collect data. Meanwhile, data is being analysed at the following stages: 1) identify and classify the original text based on the translation method, then compare the diction with the translated text, and 2) analyse and provide reasons for the translated text's incompatibility with the original text. The results showed that the most appropriate translation method to use in this novel is one that favours the target language, because translation methods that favour the source language have some diction inaccuracies. The original text's source language contains a style of language that cannot be interpreted lexically but must be interpreted contextually. The study's implication is to improve the reader's understanding of the author's intended message. مستخلص تهدف هذه الدراسة إلى تحديد وتصنيف دقة استخدام الإلقاء في رواية "اللص والكلاب" استنادا إلى نظرية بيتر نيومارك في منهجية الترجمة. يستخدم هذا النوع من الدراسة منهجا نوعيا وصفيا. يتم تنفيذ تقنيات جمع البيانات من خلال تقنيات القراءة وتحليل المستندات وأخذ العينات. وفي الوقت نفسه، يتم تحليل بيانات من خلال المراحل التالية: 1) تحديد النص الأصلي وتصنيفه بناء على طريقة الترجمة، ثم مقارنته بإملاء النص المترجم، 2) تحليل وتقديم الأسباب المتعلقة بعدم توافق النص المترجم مع النص الأصلي. أظهرت النتائج أن أنسب طريقة ترجمة مستخدمة في هذه الرواية هي الطريقة التي تفضل اللغة المستهدفة، حيث توجد بعض الأخطاء في استخدام الإلقاء كطريقة من طرق الترجمة لصالح اللغة المصدرية. تميل اللغة المصدرية في النص الأصلي إلى احتواء نمط من اللغة لا يمكن تفسيره معجميا، بل يجب تفسيره في السياق. الآثار المترتبة على هذه الدراسة هي زيادة فهم القارئ للرسالة التي يقصدها المؤلف. الكلمات المفتاحية: تحليل الإملاء؛ طرق الترجمة؛ اللص والكلاب؛ بيتر نيومارك